Verbal numeral classifiers in languages of Eastern Eurasia : A typological survey - Honkasalo, Sami; Yurayong, Chingduang (de Gruyter, 2024)
This article presents a typological survey of verbal numeral classifiers (VNCs) in languages of Eastern Eurasia. As classifiers of occurrence (e.g., to V once, to V twice), VNCs are prevalent in languages of East Asia and Southeast Asia, yet the phenomenon has been largely overlooked in typological studies that have overwhelmingly focused on the adnominal use of numeral classifiers. Analyzing a sample of 543 linguistic varieties, the study categorizes the language families of Eastern Eurasia into three groups based on their use of VNCs: 1) VNCs consistently present in all languages (e.g., Tai-Kadai); 2) VNCs present in some languages (e.g., Sino-Tibetan); and 3) VNCs consistently absent (e.g., Yukaghir). Additionally, the meanings of VNCs are shown to follow a non-random distribution by centering on certain semantic fields, such as quantifying hits with ‘verbs of violence’. The study aims to offer the first step toward an areal typological study of VNCs, highlighting the importance of including this phenomenon in future descriptive work. Peer reviewed